Spaces of contestation: Challenges, actors and expertise in the management of urban security in Greece. (May 2013) - Xenakis, Sappho; Cheliotis, Leonidas K.
Urban security has emerged as one of the key priorities in political and public life in Greece over recent years, and especially since the country fell into financial crisis in 2009. This article offers an unprecedented overview of the challenges, actors and expertise in the management of urban security in Greece, drawing attention to the political tensions that envelop them. The first section focuses on the phenomena considered to constitute core challenges for urban security in the country: from common crime, immigration and urban poverty and degradation, to social unrest, policing, far-right militias and vigilantism. The various state and non-state actors engaged in the management of urban security are then outlined, and the relationship between expertise and official policy-making is critically assessed. Objective and subjective forms of insecurity are shown to be highly contentious, responses to such insecurities are found to produce insecurities in their own right, and constraints upon non-technical expertise are identified as limiting the scope of pertinent state policy.